Tao sa tao pakikipag-ugnayan [videorecording]. ([Manila] Communication Foundation for Asia)
A reflection on why husband-wife, parent-child relationships sometimes fail which offers a solution sensitive to the feelings of others.
Keywords: Interpersonal relations; Family; Psychology